Muriqui populations reported in the literature over the last 40 years - Melo, Fabiano R.; Dias, Luiz G. (Neotropical Primates, 2005)
Aguirre (O mono Brachyteles arachnoides (E. Geoffroy). Situação Atual da Espécie no Brasil. Acad. Brasil. Ciênc., Rio de Janeiro, 1971) identified 61 localities for the occurrence of the muriqui (Brachyteles arachnoides) in the states of Bahia, Espírito Santo, Minas Gerais, Rio de Janeiro, São Paulo and Paraná. He estimated a total population of 2,791–3,226 muriquis, contrasting with a population of about 400,000 he reckoned would have existed in 1500. Accepting the position that there are two species, Aguirre’s (1971) data suggested a maximum of 996 individuals for the northern muriqui (Brachyteles hypoxanthus) and about 2,230 for the southern muriqui (B. arachnoides). Current population estimates for the northern muriqui have indicated at least 864 individuals in the wild. Data available for the southern muriqui, suggest a minimum population of about 1,300. These numbers combined approximate to the total population of 2,230 estimated by Aguirre (1971). Further population surveys for muriquis in the states São Paulo, Rio de Janeiro and Bahia are urgently needed, along with comparative studies on their basic ecology, diet and behavior in the different-sized forest fragments and the more extensive forests. Although stochastic effects could rapidly eliminate the very small isolated populations of the northern muriqui, in larger forests, persistent threats, such as hunting, could gradually but invidiously reduce those of the southern muriqui.